Natural alleles of the clock gene timeless differentially affect life-history traits in Drosophila - Andreatta, Gabriele; Montagnese, Sara; Costa, Rodolfo (Frontiers in Physiology, 2023)
Circadian clocks orchestrate a variety of physiological and behavioural functions within the 24-hour day. These timekeeping systems have also been implicated in developmental and reproductive processes that span more (or less) than 24 h. Whether natural alleles of cardinal clock genes affect entire sets of life-history traits (i.e. reproductive arrest, developmental time, fecundity), thus providing a wider substrate for seasonal adaptation, remains unclear. Here we show that natural alleles of the timeless (tim) gene of Drosophila melanogaster, previously shown to modulate flies´ propensity to enter reproductive dormancy, differentially affect correlated traits such as early-life fecundity and developmental time. Homozygous flies expressing the shorter TIM isoform (encoded by the s-tim allele) not only show a lower dormancy incidence compared to those homozygous for ls-tim (which produce both the short and an N-terminal additional 23-residues longer TIM isoform), but also higher fecundity in the first 12 days of adult life. Moreover, s-tim homozygous flies develop faster than ls-tim homozygous flies at both warm (25°C) and cold (15°C) temperatures, with the gap being larger at 15°C. In summary, this phenotypic analysis shows that natural variants of tim affect a set of life-history traits associated with reproductive dormancy in Drosophila. We speculate that this provides further adaptive advantage in temperate regions (with seasonal changes) and propose that the underlying mechanisms might not be exclusively dependent on photoperiod, as previously suggested.